2014
DOI: 10.1674/0003-0031-171.1.27
|View full text |Cite
|
Sign up to set email alerts
|

Historical Changes in Fish Assemblage Structure in Midwestern Nonwadeable Rivers

Abstract: Historical change in fish assemblage structure was evaluated in the mainstems of the Des Moines, Iowa, Cedar, Wapsipinicon, and Maquoketa rivers, in Iowa. Fish occurrence data were compared in each river between historical and recent time periods to characterize temporal changes among 126 species distributions and assess spatiotemporal patterns in faunal similarity. A resampling procedure was used to estimate species occurrences in rivers during each assessment period and changes in species occurrence were sum… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
21
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 19 publications
(24 citation statements)
references
References 41 publications
3
21
0
Order By: Relevance
“…This result supports recent research documenting ecological shifts in the opposite direction (from clear to turbid states) in which a decline in backwater specialists was observed in agriculturally impacted Midwestern rivers (Parks et al 2014). TSS concentration was lower, and vegetation coverage within Pool 8 was greater, than the highly impacted rivers in Iowa, USA, studied by Parks et al (2014). It seems likely that the expansion of vegetation beds in Pool 8 has increased areas of low water velocity within the pool, and is a possible reason for the decline in limnorheophils (Sand-Jensen 1998).…”
Section: Discussionsupporting
confidence: 91%
See 4 more Smart Citations
“…This result supports recent research documenting ecological shifts in the opposite direction (from clear to turbid states) in which a decline in backwater specialists was observed in agriculturally impacted Midwestern rivers (Parks et al 2014). TSS concentration was lower, and vegetation coverage within Pool 8 was greater, than the highly impacted rivers in Iowa, USA, studied by Parks et al (2014). It seems likely that the expansion of vegetation beds in Pool 8 has increased areas of low water velocity within the pool, and is a possible reason for the decline in limnorheophils (Sand-Jensen 1998).…”
Section: Discussionsupporting
confidence: 91%
“…This is consistent with the results of many studies demonstrating a significant positive relationship between common carp mass (non-native to North America) and TSS concentration (Meijer et al 1989;Meijer et al 1990;Havens 1991;Breukelaar et al 1994). Conversely, many studies have shown an increase in native fish biomass as TSS is reduced and vegetation coverage increases (Grift 2001;Zambrano et al 2001;Parks et al 2014). Because TSS had such a pronounced effect on the dominance between native and non-native indexed fish mass, I expect that TSS reductions will be critical to native fish conservation in the upper impounded Mississippi River.…”
Section: Discussionsupporting
confidence: 90%
See 3 more Smart Citations